Pengaruh Ekspor, Impor, Inflasi, Dan Suku Bunga Terhadap Neraca Pembayaran di Indonesia - Diokta Awagi; Agus Eko Sujianto; Lailatul Fitriana; Elvi Nurita Roisatin; Cindy Elvia Ridha Wardani (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
All records of money entering or leaving a country are kept in the balance of payments. This research was conducted with the aim of ascertaining the impact of exports, imports, inflation and interest rates on the balance of payments in Indonesia in the 2019-2022 period. The Central Statistics Agency, Bank Indonesia, and the Ministry of Trade of the Republic of Indonesia provide secondary data that is useful in a quantitative descriptive approach for the 2019-2022 period. Classical assumption testing and multiple linear regression analysis are the data analysis methods used. This research found that the variables exports (X1), imports (X2), and inflation (X3) had a negative effect on the balance of payments, while interest rates (X4) had a positive effect on Indonesia's balance of payments. Simultaneously exports, imports, inflation and interest rates influence the balance of payments in Indonesia.